2021
DOI: 10.3846/cs.2021.11244
|View full text |Cite
|
Sign up to set email alerts
|

Elementary Students’ Creative Thinking Skills in Science in the Maluku Islands, Indonesia

Abstract: Learning that encourages the development of students’ creative thinking needs to be maximized since the level of primary education, including in the disadvantaged, outermost, and frontier regions that is referred to 3T areas (terdepan, terluar, tertinggal) in Indonesia is still categorized as underdeveloped that requires special attention. The main objective of this research was to diagnose students’ creative thinking skills for four components including fluency, flexibility, originality, and elaboration on st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 39 publications
(40 reference statements)
0
21
0
2
Order By: Relevance
“…This statement is in line with the results shown, seen from the change in behavior by students. Other information comes from students, who are slow in learning, children to be annoying with friends, unfocused, and difficult to understand learning, difficulty learning concepts such as helping friends to work on tasks that require motor skills [39], [40]. Other research shows that peer tutoring develops student attitudes such as being open, active, responsible [33].…”
Section: Cycle Twomentioning
confidence: 99%
“…This statement is in line with the results shown, seen from the change in behavior by students. Other information comes from students, who are slow in learning, children to be annoying with friends, unfocused, and difficult to understand learning, difficulty learning concepts such as helping friends to work on tasks that require motor skills [39], [40]. Other research shows that peer tutoring develops student attitudes such as being open, active, responsible [33].…”
Section: Cycle Twomentioning
confidence: 99%
“…Various traditional games passed down through generations to support children's emotional and social skills developments of object control (Trajkovik et al, 2018), and positively affects the overall development of the children (Kovačević & Opić, 2014). It is very important for students to enjoy learning while exploring new media and technologies, games, and modeling (Leasa et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Problem-solving and creative thinking skills are mandatory so that students can compete globally in this revolution (Ceylan, 2020). The results of research in the field revealed that the creative thinking skills of elementary school students in the Aru Islands Regency, Indonesia were very disappointing in the moderate category (Leasa et al, 2021). Other findings also indicate that students' creative thinking skills in the original and elaboration categories are still low in high school students in Malang City, Indonesia (Batlolona et al, 2019).…”
Section: Introductionmentioning
confidence: 99%